Development of a sumo robot as educational material aimed at teaching Arduino programming (2021)
This study utilizes the elaboration of a sumo-type robot with removable parts as teaching material that facilitates the teaching-learning process of electronics and programming concepts in Arduino. A prototype was modeled and simulated with AutoCad and SolidEdge design software with which the dimensions of the mechanical structure of the prototype was created. An Arduino board was used as a control element in order to effectively manipulate the sensors and actuators that make up the robot. The construction of the prototype utilized printed 3D parts which were compared to the original design parameters of the robot. The developed robot has educational guides for the mechanical and electronic assembly as well as programming guides for its correct operation. As a result, the sumo robot meets the technical and pedagogical requirements to be used as teaching material.